In vivo measurement of breast muscle in broiler chickens by means of CT - Andrássyné Baka, Gabriella; Romvári, Róbert; Petrási, Zsolt (Acta Agraria Kaposváriensis, 1999)
In this investigation 72 Arbor Acres genotype broiler chickens were subjected to CT examination at the ages of 2, 3, 4, 5, 6, 7 and 8 weeks. Tried slaughter was then performed and the weight of the filleted breast muscle was recorded. In the evaluation of the CT images produced (6–11 images per broiler) the volume of the breast muscle was determined. The largest muscle area was measured in the plane intersecting the second or the third rib (2nd and 8th week, 6.3 and 34 cm2 respectively). The values obtained for the volume of the breast muscle increased from 21.9 cm3 at 2 weeks to 194 cm3 by the 8th week of life. When the weight of the filleted breast muscle was estimated on the basis of the CT images r values ranging between 0.46 and 0.88 were calculated. The results obtained indicate that the spatial configuration of the breast muscle changes with age. In the first weeks of life muscle growth in the plane intersecting the second and third rib, taken with birds examined lying in a prone position, is characteristic; with advancing age this growth shifts along the longitudinal axis of the animal in the caudal direction.